Assessment of intimate partner violence abuse ratings by recently abused and never abused women - Helen E. Straus; Elizabeth H. Guonjian; Errick Christian; Rebecca R. Roberts (BMC, 2020)
Abstract Background There are a paucity of directly reported intimate partner violence survivors' experiences, especially in women of color. This study measures recently/currently abused women's ratings of varied abuse events compared to ratings from never abused women. Methods Women in a single, urban, public hospital emergency department (ED) were screened for intimate partner violence using the Abuse Assessment Screen (AAS). Two groups were identified - women abused within 1 year by an intimate partner or family member and those who screened negative for abuse. Using a two-group longitudinal survey and interview format, women completed visual analog scale ratings (0-100) for each of 20 abuse events/types. For analysis, each abuse type was placed on the 0-100 scale according to its designated rating. Results Average age of participants in the abuse group (n = 30) was 33. Never abused women averaged age 50 (n = 32). The majority of participants were African-American: abused 67% and never abused 94%. Abused women rated name-calling (p < 0.02) and put-downs (p < 0.01) as more severe than never abused women. Other non-physical and physical forms of abuse such as threats, control, burns or forced sex were perceived more similarly between groups. Conclusions Abused women perceive verbal abuse events differently compared to never abused women.